A case of angiosarcoma arising from internal jugular vein. Issue 1 (February 2015) - Kishimoto, Ippei; Kikuchi, Masahiro; Shinohara, Shogo; Fujiwara, Keizo; Kanazawa, Yuji; Tona, Risa; Harada, Hiroyuki; Usami, Yu; Naito, Yasushi
Abstract Primary angiosarcoma is a rare disease with a poor prognosis. It most commonly arises in the head and neck region; localization in the deep soft tissue of the neck is extremely rare. We herein present a case of angiosarcoma derived from the right internal jugular vein. A 79-year-old man presented with a 1-month history of a growing right neck mass. Computed tomography, magnetic resonance imaging, positron emission tomography-computed tomography, and fine-needle aspiration cytology revealed a malignant tumor of unknown origin. Right neck dissection was performed for both diagnosis and therapy. Immunostaining of the resected tumor cells revealed positivity for CD31, CD34, factor VIII-related antigen, and D2–40, which allowed for a definitive diagnosis of angiosarcoma. Postoperative radiotherapy (66 Gy) was performed on the right neck, including the surgical bed and upper mediastinum. The patient was followed up for 10 months with no recurrence. Only six cases of angiosarcoma arising in the deep soft tissue of the neck have been reported in the English-language literature. The present report is the first to describe angiosarcoma arising from the internal jugular vein.